Dilema Sistem Pemilihan Umum 2009 - Nurhasim, Moch (Pusat Penelitian Politik, 2009)
The 2009 election is regarded as the worst election in the history of the reform era elections particularly in the quality of its implementations and results This happened as a consequence of systemic problems particularly the inconsistency ofUU No 10 2008 with its implementation technical rules The change of election system has been one of the main causes since the draft of UU No 10 2008 is not a full opened proportional system but rather a semi opened system that is changed further by the Constitution Court Mahkamah Konstitusi into a full opened proportional system This change that is not followed by the change of its articles has made the implementation of the 2009 election was full of dilemmas and deficiencies.